Can I Discharge My Stroke Patient Home After Inpatient Neurorehabilitation? LIMOS Cut-Off Scores for Stroke Patients “Living Alone” and “Living With Family” - Ottiger, Beatrice; Lehnick, Dirk; Pflugshaupt, Tobias; Vanbellingen, Tim; Nyffeler, Thomas (Frontiers in Neurology, 2020)
Background Discharge planning of stroke patients during inpatient neurorehabilitation is often difficult since it depends both on the patient's ability to perform activities of daily living (ADL) and the social context. The aim of this study was to define ADL cut-off scores using the Lucerne ICF-based multidisciplinary observation scale (LIMOS) that allow the clinicians to decide whether stroke patients who "live alone" and "live with a family" can be discharged home or must enter a nursing home. Additionally, we investigated whether age and gender factors influence these cut-off scores. Methods A single-center retrospective cohort study was conducted to establish cut-off discharge scores for the LIMOS. Receiver-operating-characteristics curves were calculated for both patient groups "living alone" and "living with family" to illustrate the prognostic potential of the LIMOS total score with respect to their discharge goals (home alone or nursing home; home with family or nursing home). A logistic regression model was used to determine the (age- and gender-adjusted) odds ratios of being released home if the LIMOS total score was above the cut-off. A single-center prospective cohort study was then conducted to verify the adequacy of the cut-off values for the LIMOS total score. Results A total of 687 stroke inpatients were included in both studies. For the group “living alone” a LIMOS total score above 158 indicated good diagnostic accuracy in predicting discharge home (sensitivity 93.6%; specificity 95.4%). A LIMOS total cut-off score above 130 points was found for the group "living with family" (sensitivity 92.0%; specificity 88.6%). The LIMOS total score odds ratios, adjusted for age and gender, were 292.5 (95% CI: (52.0 – 1645.5)) for the group “living alone” and were 89.4 (95% CI: (32.3 – 247.7)) for the group “living with family”. Conclusion Stroke survivors living alone needed a higher ADL level to return home than those living with a family. A LIMOS total score above 158 points allows a clinician to discharge a patient that lives alone, whereas a lower LIMOS score above 130 points can be sufficient in a patient that lives with a family. Neither age nor gender played a significant role.